Angiostatic versus angiogenic chemokines in IPF and EAA - Martina, Sterclova; Martina, Vasakova; Monika, Metlicka; Jan, Pavlicek; Libor, Kolesar; Ilja, Striz (Respiratory medicine, 2009)
BACKGROUND: Extrinsic allergic alveolitis (EAA) and idiopathic pulmonary fibrosis (IPF) share the presence of varying degree interstitial involvement and fibrosis. Vascular changes were often reported to accompany the development of fibrosis. OBJECTIVES: The aim of our study was to examine the differences in angiostatic and angiogenic chemokine milieu in both diseases. Correlations between chemokine levels in bronchoalveolar lavage fluid (BALF), expression of chemokine receptors on CD4+ T cells (CXCR2, CXCR3) in BALF and HRCT pattern of the diseases were investigated. METHODS: Sixteen patients with chronic EAA and 8 with IPF were enrolled to the study. Concentrations of interleukin (IL)-8, epithelial neutrophil activating protein (ENA)-78, interferon-gamma-inducible protein (IP)-10 and interferon-inducible T cell alpha chemoattractant (I-TAC) in BALF supernatants were quantified using Fluorokine MultiAnalyte profiling. RESULTS: There was no significant difference in the BALF chemokine levels between the EAA and IPF group. IL-8 BALF concentrations correlate with the extent of fibrosis in both EAA and IPF (p<0.01). The IP-10 BALF concentrations do not correlate either with the HRCT alveolar or interstitial score and should be evaluated in the relationship with the disease course. CONCLUSIONS: Both IL-8 and ENA-78 probably play a different role in IPF and chronic EAA pathogenesis. While we suggest ENA-78 as the marker of at least partial reversibility of the lung impairment in the EAA patients, IL-8 could be rather an indicator of continuous exposition to provoking agent in EAA patients. IL-8 might serve as a potential marker of early phase of IPF.
Keywords: dospělí; Chemokine CXCL5; plíce; Prognosis; Prospective Studies; senioři nad 80 let; bronchoalveolární lavážní tekutina; Humans; lidé středního věku; Interleukin-8; prospektivní studie; Aged, 80 and over; Middle Aged; Young Adult; chemokin CXCL11; mladý dospělý; Alveolitis, Extrinsic Allergic; receptory chemokinů; prognóza; Bronchoalveolar Lavage Fluid; mužské pohlaví; Chemokine CXCL11; Adult; Lung; Receptors, Chemokine; hypersenzitivní pneumonitida; Chemokine CXCL10; interleukin-8; biologické markery; Chemokines; ženské pohlaví; idiopatická plicní fibróza; lidé; chemokiny; Idiopathic Pulmonary Fibrosis; Biomarkers; Aged; senioři; chemokin CXCL10; chemokin CXCL5; Male; Female